I want to believe they really care: how complaining customers want to be treated by frontline employees - Thorsten Gruber (2011)
Purpose – Using a realist perspective, this paper investigates how complaining customers want to be treated by frontline employees in personal complaint handling encounters. For this purpose, an exploratory research study using the qualitative laddering interviewing technique was regarded as appropriate as it allows researchers to gain a deeper insight into an underdeveloped research subject. Following realist thinking and terminology, the exploratory study aims to develop a deeper understanding of the so-called micro structures of complaining customers. Design/Methodology/Approach – A semi-standardized qualitative technique called laddering was used to reveal the cognitive structures of complaining customers. In total, laddering interviews with 40 respondents with complaining experience were conducted. Findings – The research shows that the most important attributes for complaining customers are the contact employees’ authenticity, competence, and active listening skills. These concepts are linked with several consequences and values such as “Justice”, “Well-Being”, and “Security”. Research limitations/implications – Due to the exploratory nature of the study in general and the scope and size of its sample in particular, the findings are tentative in nature. As the study involved students from one university, the results cannot be generalized beyond this group even though in this case the student sample is likely to represent the general buying public. Practical implications – If companies know what complaining customers expect, frontline employees may be trained to adapt their behaviour to their customers’ underlying expectations, which should have a positive impact on customer satisfaction. For this purpose, the paper gives several suggestions to managers to improve active complaint handling and management. Originality/value – Our findings enrich the existing limited stock of knowledge on complaint satisfaction by developing a deeper understanding of the attributes that complaining customers expect from frontline employees, as well as the underlying logic for these expectations. Revealing the important role of employee authenticity adds to our knowledge on complaint satisfaction. Another strong contribution of this paper lies in the finding that all the identified concepts must not been seen in strict isolation, as in previous research, but have to be understood as a network of interrelated concepts: The attributes of frontline employees have several important consequences for customers (e.g. the feeling of being taken seriously), which are then linked to consumers’ personal values and basic motivations (e.g. perceptions of justice).